Transformation of Traditional Msme Business Models in Gorontalo City Due to Digitalization: Analysis of Adaptation and Challenges in the Digital Economy Era: JEL Classification: L26, M21, O33, D22, R11 - Sitti Husna Noviana Djou; Amnatia R Abdullah (Newinera Publisher, 2025)
The business environment has undergone significant changes due to global digitalization, and MSMEs in the city of Gorontalo are no exception. The difficulties faced by MSMEs in surviving and maintaining sustainability have become a significant issue requiring attention from various stakeholders. However, digitalization also provides opportunities for MSMEs to increase their market share and enhance their competitiveness. Therefore, the aim of this research is to understand how digitalization has transformed the conventional business models of MSMEs, identify strategies for adaptation, and comprehend the challenges that arise during this process. This study examines MSMEs in the city of Gorontalo using a case study methodology and a qualitative approach. Data analysis will be conducted using the Digital Transformation Framework to examine the factors that drive and hinder the digitalization of SMEs, the Dynamic Capabilities Framework to assess how easily SMEs adapt to digital changes, and the Business Model Innovation theoretical approach to understand the changes in business model elements of SMEs. The research results show that (1) Digitalization has brought significant changes to the business models of traditional MSMEs. The use of BMI suggests that digitalization impacts not only marketing and distribution aspects but also product innovation, operational efficiency, and customer relationships. (2) The main factors influencing the level of adaptation include the desire to expand markets, improve efficiency, and keep up with the times. (3) The main challenges faced by traditional MSMEs in the process of business transformation towards digital are production capacity, logistics costs, technology management, customer response, and promotion costs.